2019
DOI: 10.1007/s13318-019-00551-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pharmacokinetic Outcomes of Peak–Trough-Based Versus Trough-Based Vancomycin Therapeutic Drug Monitoring Approaches: A Pragmatic Randomized Controlled Trial

Abstract: BackgroundVancomycin therapeutic drug monitoring (TDM) is based on achieving 24-h area under the concentration–time curve to minimum inhibitory concentration cure breakpoints (AUC24/MIC). Approaches to vancomycin TDM vary, with no head-to-head randomized controlled trial (RCT) comparisons to date.ObjectivesWe aimed to compare clinical and pharmacokinetic outcomes between peak–trough-based and trough-only-based vancomycin TDM approaches and to determine the relationship between vancomycin AUC24/MIC and cure rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 69 publications
0
23
0
1
Order By: Relevance
“…To determine the AUC in a clinical setting, either a peak and trough sample or Bayesian forecasting using a single sample has been recommended 77 . A recent study found that considering both peak and trough levels showed better therapeutic cure rates compared with only trough levels, although this result requires confirmation in larger studies 79 . Neely and colleagues showed that AUC‐based vs. trough‐based TDM was superior with regard to reduction of nephrotoxicity (<1% vs. 8%), and shorter therapy time (4.7–5.4 vs. 8.2 days) 63 .…”
Section: Anti‐infectives For Which Precision Dosing Improves Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the AUC in a clinical setting, either a peak and trough sample or Bayesian forecasting using a single sample has been recommended 77 . A recent study found that considering both peak and trough levels showed better therapeutic cure rates compared with only trough levels, although this result requires confirmation in larger studies 79 . Neely and colleagues showed that AUC‐based vs. trough‐based TDM was superior with regard to reduction of nephrotoxicity (<1% vs. 8%), and shorter therapy time (4.7–5.4 vs. 8.2 days) 63 .…”
Section: Anti‐infectives For Which Precision Dosing Improves Outcomesmentioning
confidence: 99%
“…77 A recent study found that considering both peak and trough levels showed better therapeutic cure rates compared with only trough levels, although this result requires confirmation in larger studies. 79 Neely and colleagues showed that AUC-based vs. trough-based TDM was superior with regard to reduction of nephrotoxicity (<1% vs. 8%), and shorter therapy time (4.7-5.4 vs. 8.2 days). 63 Nonetheless, more research is required to potentially further optimize the AUC target for vancomycin, as a recent systematic meta-analysis found that the sensitivity and specificity was 0.77 (95% confidence interval (CI), 0.67-0.84) and 0.62 (95% CI, 0.52-0.71), respectively, for the primary outcome variable mortality.…”
Section: Glycopeptidesmentioning
confidence: 99%
“…The study suggested that a TDM-guided Bayesian-based approach should be considered an invaluable tool for clinicians to appropriately monitor real-time vancomycin therapy in critically ill patients [ 17 ]. In this study, peak and trough vancomycin concentrations were measured in over half the patients for whom the previous study showed peak-trough based vancomycin TDM improved the therapeutic cure rate [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Sulaiti reported the importance of peak drug concentration for vancomycin dosing. Peak-trough TDM approach improves the vancomycin-associated cure rate in patients treated with vancomycin for Gram-positive infections (12). The correct timing of blood draw is the major practical problem of the interpretation of peak plasma drug concentrations.…”
Section: Discussionmentioning
confidence: 99%